2014
DOI: 10.1108/ijlm-05-2013-0050
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of logistics integration on supply chain performance

Abstract: Purpose – The purpose of this paper is to analyze the impact of individual logistics-related factors, namely, supplier involvement (SI), length of supplier relationship (LSR), use of information technology (IT), and logistics integration (LI) on a firm's supply chain performance (SCP) and test for the mediating effect of LI in a multi-country survey conducted in Brazil, Korea and India. The paper also develops a composite variable, supply chain competency (SCC), as an overall measure of the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 92 publications
(104 reference statements)
3
37
1
1
Order By: Relevance
“…At last, II is the third level of integration as it is the substance between SI and CI, and it is difficult to accomplish either SI or CI without II. Huo 2012, Gimenez et al (2012), Alam et al (2014) studies are consistent with above result. Results have also shown that SI was having the most remarkable impact on organisational performance, trailed by CI, lastly II.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…At last, II is the third level of integration as it is the substance between SI and CI, and it is difficult to accomplish either SI or CI without II. Huo 2012, Gimenez et al (2012), Alam et al (2014) studies are consistent with above result. Results have also shown that SI was having the most remarkable impact on organisational performance, trailed by CI, lastly II.…”
Section: Discussionsupporting
confidence: 85%
“…In recent years, manufacturing organisations tend to form a stable relationship with their suppliers to deal with the variance in demands of the customers and lessening the production cycle time and delivery time defined by the firm and the customers (Bagchi et al, 2005;Zhao et al, 2011;Huo, 2012). Suppliers now are progressively associated with creating the products to promote production and remaining neighbouring to the customer (Kim, 2009;Alam et al, 2014). Therefore, the investigation characterised supplier integration (SI) as the procedure of cooperation among partners and organisation that encourage the distribution of data, experience, materials and services.…”
Section: Supply Chain Integration Elementsmentioning
confidence: 99%
“…Organizational members are learning to "march to the beat of the same drummer" which is helping to meet the everchanging demands. Cross-functional integration is essential for providing and processing quality information and developing effective decision-making processes in the relationship with different agents along the supply chain (Mollenkopf et al, 2000;Alam et al, 2014).…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Zhang and Okoroafo (2015) in a conceptual frame work for 3PL, discussing the importance of integration, mentioned that in a supply chain the 3PL must have the integrating capability to share and receive information with their clients in order to be able to improve the level of their service. Alam, Bagchi, Kim, Mitra & Seabra (2014) studying the impacts of supplier involvement, length of relationship, information technology and logistics integration competency on the success of supply chain management found that, in comparison to other factors, logistics integration has very significant impact on the success of supply chain and as a moderating factor it positively improves the impact of other factors on the success of logistics value chain.. The whole literature reviewed and referred above, no doubt, emphasized the importance of integration competency for the success of chain partners but what lacked here was the recipe or strategy how to achieve integration competency.…”
Section: Integration Competencymentioning
confidence: 99%